PENGARUH PENGGUNAAN MODEL PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR IPS TERPADU SISWA KELAS VIII SEMESTER GENAP SMP NEGERI 2 PEKALONGAN - Fitriasari, Reni; Dewi, Tiara Anggia (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
The purpose of this study was to determine the effect of using scramble learning models on integrated social studies learning outcomes of class VIII students in the even semester of SMP 2 Pekalongan in the academic year 2017/2018". This research is quantitative in nature that examines the influence of independent variables, namely scramble learning model, and the dependent variable is integrated social studies learning outcomes. The method used the experimental method Quasi Experimental Design with the research design Nonequivalent Control Group Design. Based on the results of the study, it is evidenced by the calculation of data analysis it can be seen that the value of tcount> t table at the significance level of 5% is 5.64> 1.70. After being treated with scramble learning model the learning outcomes increased by 24 students or 70.59% including the complete category, and 10 students or 29.41% including the incomplete category. Thus the hypothesis is accepted, indicating that the scramble learning model gives a positive influence on the learning outcomes of integrated social studies students of class VIII even semester of SMP 2 Pekalongan in the academic year 2017/2018.      Keywords: Scramble Learning Model, Learning Outcomes.